2023
DOI: 10.1186/s12866-023-02896-9
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhea accompanies intestinal inflammation and intestinal mucosal microbiota dysbiosis during fatigue combined with a high-fat diet

Abstract: Objective It was reported fatigue or a high-fat diet triggers diarrhea, and intestinal microbiota may play central roles in diarrhea. Therefore, we investigated the association between the intestinal mucosal microbiota and the intestinal mucosal barrier from fatigue combined with a high-fat diet. Method This study divided the Specific pathogen-free (SPF) male mice into the normal group (MCN) and the standing united lard group (MSLD). The MSLD group… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The ovaries of mice were dissected and removed under aseptic conditions, fixed in 4% paraformaldehyde solution and stored at room temperature. According to gradient dehydration, paraffin embedding after xylene transparency, made into 5um sections, the mouse ovary tissue sections were routinely deparaffinized, stained with hematoxylin and eosin (HE) solution sequentially, sealed with neutral gum, and photographed under the microscope for observation ( Liu et al., 2023 ; Zhou et al., 2024 ).…”
Section: Methodsmentioning
confidence: 99%
“…The ovaries of mice were dissected and removed under aseptic conditions, fixed in 4% paraformaldehyde solution and stored at room temperature. According to gradient dehydration, paraffin embedding after xylene transparency, made into 5um sections, the mouse ovary tissue sections were routinely deparaffinized, stained with hematoxylin and eosin (HE) solution sequentially, sealed with neutral gum, and photographed under the microscope for observation ( Liu et al., 2023 ; Zhou et al., 2024 ).…”
Section: Methodsmentioning
confidence: 99%
“…This database prioritised druggable targets through the integration of information gathered through text mining, expert curation, drug-gene interactions, as well as gene function. The Enrichr platform 9 analyzed and visualized data (52).…”
Section: Protein-protein Interaction and Druggability Predictionmentioning
confidence: 99%
“…For example, pulmonary rehabilitation helps the respiratory symptoms of chronic obstructive pulmonary disease and also fatigue (6). Exercise therapy and psychological therapies, notably cognitive behavior therapy, offer some evidence of success in the treatment of fatigue caused by cancer, inflammatory illnesses (e.g., inflammatory bowel disease, rheumatoid arthritis) (7)(8)(9), and neurological disorders (for example, multiple sclerosis, myasthenia gravis) (10,11). Exercise may improve fatigue and function related to fibromyalgia (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Non-diarrhea patients show a higher abundance of Bacteroides and a lower abundance of Firmicutes ( Sakai et al, 2021 ; Zhu et al, 2023 ). Mice with diarrhea caused by a high-fat diet in fatigue state have dysbacteriosis, Limosilactobacillus is significantly reduced, and Anaerotruncus is significantly increased ( Liu et al, 2023 ). Additionally, previous research by our team revealed that diarrhea with kidney-yang deficiency syndrome changed the structure and function of the intestinal content microbiota in mice, featuring enriched Lactobacillus intestinalis and Bacteroides acidifaciens ( Li et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%